Exploring customer satisfaction as a mediator between the impact of Uniqlo customer engagement and corporate sustainability reputation on the purchase intention of DLSU RVR-COB students regarding sustainable clothing - Go, John Jonathan T. (Animo Repository, 2023)
Fast fashion is the latest trend in the fashion industry. The manufacturing of fast fashion products is at a faster production cycle to keep up with the dynamic trends in the market. These companies use cheaper materials and labor to create cheap but lower quality products which have given them a notoriety for negative impact on environment. UNIQLO is among the fast fashion companies that have decided to break away from fast fashion practices. This study focused on investigating the customer engagement and corporate sustainability reputation of UNIQLO consumers as mediated by customer satisfaction. Main concepts included two independent variables of customer engagement, dependent variable of purchase intention, and mediator of customer satisfaction. To gather data, the researchers took a quantitative approach and established a Google Forms survey questionnaire including items adapted from scales of measurement in past studies. A total of 449 responses were obtained from students belonging to the various departments of the Ramon V. del Rosario - College of Business. Then, the data obtained was analyzed through statistical tests which included Cronbach’s alpha, Pearson’s correlation, simple linear regression, multiple linear regression, and mediation analysis. The results highlighted that, individually, customer engagement, corporate sustainability reputation, and customer satisfaction have a significant correlation and impact on purchase intention. Furthermore, customer engagement and corporate sustainability reputation, when together, can significantly influence purchase intention. Lastly, customer satisfaction has been observed to have a partial mediating effect to the relationship of customer engagement and corporate sustainability reputation on purchase intention.